Answer: First option.
Explanation:
1. To solve this problem you can applly the quadratic formula, which is shown below:
![x=\frac{-b+/-\sqrt{b^(2)-4ac}}{2a}](https://img.qammunity.org/2020/formulas/mathematics/high-school/1d8kum03w6i79ky98lyc0pvno85vcpr5w4.png)
2. The quadratic equation is:
![x^(2)-4x-9-29=0\\x^(2)-4x-38=0](https://img.qammunity.org/2020/formulas/mathematics/high-school/i0cv08siouhboeix555u6lfxlu5cgef1wt.png)
3. Then:
a=1
b=-4
c=-38
4. Therefore, when you substitute these values into the quadratic formula, you obtain the following result:
![x=\frac{-(-4)+/-\sqrt{(-4)^(2)-4(1)(-38)}}{2(1)}](https://img.qammunity.org/2020/formulas/mathematics/high-school/vlfkjgv6rpp7rajz6ms8sia860sa8w3ypj.png)
x=2±√42